A track chart of H.M. sledges Perseverance & Resolute : the dotted line shews the returning track. The black Coast line is Sir E. Parry's: the red is that discovered, or laid down by Lt. Mc.Clintock, & the blue by Mr. Bradford whilst detached between 11th May, & 12th June. Only those Coasts which have been searched are shaded. F. L. Mc.Clintock / Day & Son Lithrs. to the Queen. (Hydrographic Office of the Admiralty, 1852)
Color;